Violencia y memoria en el periodismo narrativo peruano. De dónde venimos los cholos y El origen de la hidra. Crimen organizado en el norte del Perú - Linares Ángeles, Andrea Verina (2020)
Narrative journalism books are characterised by transcending the stories they tell, and by capturing the most important aspect of a writer: their style and way of communicating life experiences. The good use of literary resources has allowed the creation of entertaining, credible and non-fiction chronicles. This investigation studies the books De dónde venimos los cholos and El origen de la hidra. Crimen organizado en el norte del Perú, which recreate events of violence in the country, aiming to unravel the styles of its authors, and reflect on the importance of journalistic non-fiction in consolidating a memory of serious social problems. Based on the characteristics of the so-called new non-fiction, literary or narrative journalism, this research identifies the resources of literary realism used in the publications mentioned, and the type of collective memory that they reconstruct from the facts, customs and behaviours of the community. It is concluded that the personal vision of each author as the message transmitter provides the reader with a taught memory, that is, a type of memory that aims to provoke reflections on events of violence inherited generation after generation in Peru.